The Systemic Exclusion of Native Americans from Cancer Clinical Trials - HW, Cayatineto; CS, Clyde; GA, Yazzie; G, Selassie; J.A, de Soto (Jour Med Resh and Health Sci, 2021)
Introduction: A major source of health care disparities derives from the underrepresentation of ethnic minorities in clinical trials. The inclusion of ethnic minorities is necessary to generalize the results in terms of efficacy and toxicology of medications in cancer treatment. Methodology: In this retrospective study, 80 cancer clinical trials with an aggregate of 278,470 participants performed within the last ten years were selected at random. The number of ethnic minorities participating and inclusion of them in the results were evaluated. Results: Only, 42.5% of cancer clinical trials reported the ethnic background of participants in their trials while even less 5% reported the efficacy or toxicology of the therapeutic intervention for ethnic minorities. Whites, Hispanics, African Americans, and Native Americans make up 60.1%, 18.5%, 13.4% and 1.5% of the population they made up 85.3%, 2.54%, 7.6% and 0.12% of the participants that reported ethnicity, respectively. Out of 278,470 participants in cancer clinicals trials only 133 (0.048%) could be identified as Native American . Conclusion: Native Americans were nearly completely excluded from cancer clinical trials. African Americans and Hispanics were greatly underrepresented. Cancer Clinical trials may not be generalizable and have been inherently racist in the United States. This has led to the unnecessary death and suffering of Native Americans from cancer.